Characterization Of Propagation In Wireless Sensor Network (Wsn) For Aquaculture Application - Hasbullah, Khadijah (2016)
This project proposed propagation characteristics in WSN for aquaculture application. It emphasized on optimum distance estimation in the development of a strong network for delivering data in WSN. Stage 1 of the research was aimed to select the type of antenna and its optimum transmission angle, and also to determine the optimum transmission distance between coordinator and sensor node for the proposed topology. The type of antenna and its best transmission angle were achieved by investigating the effect of antennas orientation on signal strength. The radiation patterns plotted from the data showed that chip antenna was a better directional antenna and most suitable for sensor node application with best transmission angle of 90°. Dipole antenna that had good RSSI reading at all angle was suitable to be used for coordinator. The study on transmission distance enabled the estimation of optimum distance between coordinator and sensor node be made. Distance estimation was calculated using the log of distance equation generated from the RSSI versus log of distance graph plotted from the experiment data. The percentage error for the estimated distance when compared with the measured distance were 6.2%, 18.8% and 22% for dense vegetation area, small trees and bushes area and building area respectively. The result of the field study to test the network topology constructed based on the result of research stage 1 showed positive result, proving that the optimum antenna orientation used and the application of the discovered log-distance equation in estimating the optimum distance were appropriate.